Comparative analysis of educational management as an agent of change and innovation to the complex educational environments, for organizations: Nuevo Mundo High School and Piedades Sur´s Technical High School, San Ramon - Barquero González, María Alejandra (2013)
This article discusses the comparative analysis of educational management as an agent of change and innovation to the complex educational environments in organizations: Nuevo Mundo High School and Piedades Sur´s Technical High School, San Ramon. To obtain the data we applied a questionnaire to a sample of teachers and students as well as the directors of both institutions. Besides we used multiple secondary sources to build a context of interpretation that would locate the particular case of these two schools, within the reality of educational management as an agent of change and innovation.The principle guiding this study is that it is now essential to implement techniques and strategies, where it is required active leaders with human guidance and clarity in educational management that must be addressed not only in the present but also in the future.Finally, with the results and conclusions obtained through the analysis of the data, we performed a project proposal called "Week of integration: promoting a culture of peace", which purpose is to be an alternative of innovation and change, which generates a space of coexistence between the community and the institution, as well as promote their experience of values among community members.